The Influence of Islamic Education Policy On The Implementation of Multiculturalism at The Al-Asholah Foundation - Bafadhal, Abdurrahman; Sulhan, Ahmad; Wahyudiati, Dwi (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This study aims to explain whether there is an influence of Islamic education policies on the application of multiculturalism at the Al-Asholah Sumbawa foundation. The data collection technique used the observation method, with a questionnaire instrument. Based on the normality test obtained a value of 0.067>0.05, the data is normally distributed. Based on the homogeneity test obtained 0.845>0.05 this indicates data is homogeneous. Based on the T test, a significant value of 0.001 <0.05 is obtained, there is an influence of variable X on variable Y, and the F test obtained a significant value of 0.001 <0.05, this indicates that simultaneously there is an influence of variable X on variable Y. It can be concluded that there is an influence of Islamic education policy on the application of multiculturalism at the Al-Asholah Sumbawa Foundation. This can be seen from the significant value obtained in the T test and F test of 0.001 <0.05, which means that the alternative hypothesis is accepted and the null hypothesis is rejected.